The Effect of Using Crude Enzymes of Cattle Rumen Contents as Bioactivator on the content of Dry Matter, Organic Matter and Crude Protein Content of Palm oil Fronds - Tri Astuti; Syahro Ali Akbar; Fajri Basyirun; Fauzi Maulana; Harissatria harissatria (Bantara Journal of Animal Science, 2022)
This research aims to evaluation the effect using of crude enzymes base on the rumen contents of cattle as bio activators with different doses and incubation length on the dry matter, organic matter, and crude protein content of palm oil fronds to be used as ruminants feed.  The completely factorial randomized design with 3 replications for each treatment was used in this study. Factor A was the incubation length of the palm fronds, where A1 = 7 days, A2 = 14 days. Factor B dose of crude enzyme; B1 = 5%, B2 = 10%, B3 = 15%. Parameters observed were dry matter content, organic matter, crude protein. The results showed that there was no interaction effect (p>0.05) between incubation length and different doses of crude enzymes on dry matter, organic matter, and crude protein content of palm fronds. The highest dry matter content was 93.89%, the highest organic matter was 89.22% and the highest crude protein content was 11.04%. The best results in this study were at a dose of 10% treatment with an incubation period of 7 days.